Seasonal Variation in Viral Infection Rates and Cell Sizes of Infected Prokaryotes in a Large and Deep Freshwater Lake (Lake Biwa, Japan) - Shen, Shang; Shimizu, Yoshihisa (Frontiers in Microbiology, 2021)
As viruses regulate prokaryotic abundance and the carbon cycle by infecting and lysing their prokaryotic hosts, the volume of infected prokaryotes is an important parameter for understanding the impact of viruses on aquatic environments. However, literature regarding the seasonal and spatial variations in the cell volume of infected prokaryotes is limited, despite the volume of the prokaryotic community varying dynamically with season and water column depth. Herein, we conducted a field survey for two annual cycles in a large and deep freshwater lake (Lake Biwa, Japan), where large prokaryotes inhabit the deeper layer during the stratified period. We used transmission electron microscopy to reveal the seasonal and spatial variation in the frequency of viral infection and cell volume of infected prokaryotes. We found that the viral infection rate in the surface layer increased when estimated contact rates increased during the middle of the stratified period, whereas the infection rate in the deeper layer increased despite low estimated contact rates during the end of the stratified period. In addition, in the deeper layer, the fraction of large prokaryotes in the total and infected prokaryotic communities increased progressively while the number of intracellular viral particles increased. We suggest different ways in which the viral abundance is maintained in the two water layers. In the surface layer, it is speculated that viral abundance is supported by the high viral infection rate because of the high activity of prokaryotes, whereas in the deeper layer, it might be supported by the larger number of intracellular viral particles released from large prokaryotes. Moreover, large prokaryotes could contribute as important sources of organic substrates via viral lysis in the deeper layer, where labile dissolved organic matter is depleted.